The defence of the realm the authorized history of MI5 - Andrew, Christopher M. (London Allen Lane, 2009)
To mark the centenary of its foundation, the British Security Service, MI5, opened its archives to an independent historian. The Defence of the Realm, the book which results, is an unprecedented publication, It reveals the precise role of the Service in twentieth-century British history, from its foundation by Captain Kell of the British Army in October 1909 to root out 'the spies of the Kaiser' up to its present role in countering Islamic terrorism. It describes the distinctive ethos of MI5, how the organization has been managed, its relationship with the government, where it has triumphed and where it has failed. In all of this, no restriction has been placed on the judgements made by the author.
Includes bibliographical references (p. [989]-1004) and index.
Keywords: Great Britain. MI5--History.